Thinking, Longing, and Nearness: In Memoriam Bernd Jager (1931-2015) - Seamon, David (My University, 2017)
Phenomenological psychologist Bernd Jager died in Montreal on March 30, 2015, at the age of 83. For many readers of Phenomenology & Practice, Jager was a greatly admired scholar who regularly attended and presented at the annual nternational Human Science Research conferences. His home institution, the Department of Psychology at the University of Quebec at Montreal, hosted the 2012 conference in which Jager played an instrumental role in organizing and hosting that event.
Citation: Seamon, D. (2016). Thinking, Longing, and Nearness: In Memoriam Bernd Jager (1931-2015). Phenomenology & Practice, 10(1), 47-58. Retrieved from <Go to ISI>://WOS:000379143500004
Keywords: Philosophy